Marriage rate in Czech countries in 1950 – 2011 - Doskočilová, Veronika; Langhamrová, Jitka, 1958-; Kačerová, Eva; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2013)
The bachelor thesis is titled Marriage rate in Czech countries in 1950 -- 2011. Its primary goal is to explore marriage coefficients and valorize its development, changes and course of them. The marriage rate is presented in form of coefficients of marriage. In the beginning, the thesis inquire into development of marriage in 1950 -- 2011. It describe changes in development and the main factors which have an influence to marriage. It describe it up to the present. The thesis inquires into development of marriage rate. It describe the marriage rate for men and women separated. It describes the marriage rate and differences between men and women. In the next part thesis describe seasonality marriage rate. It is presented in the form of seasonal indexes marriage rate. There are also describes changes. Especially in the cultural traditions and superstitions. The next thesis inquires into marriages of singles. It is presented in the form of marriage rate of singles. It describes size of part which participates on marriage. And if it is still the main part, as it was in past. The last part of the thesis describes marriage rate of not-married women.
Vedoucí práce: Jitka Langhamrová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: statistické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses